Improving silage quality - K.K. Bolsen; B.E. Brent; M.K. Siefers; G.L. Huck; J.E. Turner; Matthew A. Young (Kansas Agricultural Experiment Station Research Reports, 1996)
Results at Kansas State University from over 200 laboratory-scale trials and 28 farm-scale trials showed that bacterial inoculants consistently improved preservation efficiency and nutritive value of the ensiled material. In contrast, anhydrous ammonia or urea decreased dry matter recovery and production per ton of crop ensiled. Economic analysis also favored the use of bacterial inoculants over nonprotein nitrogen additives. Research conducted using corn, sorghum, and alfalfa silages showed that sealing the exposed surface dramatically reduced top spoilage losses in bunker, trench, or stack silos.
Keywords: Cattlemen& #x27; s Day; 1996; Kansas Agricultural Experiment Station contribution; no. 96-334-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 756; Beef; Silage; Inoculant; Nonprotein nitrogen; Top spoilage